Multiplexed Functional Assessment of Genetic Variants in CARD11. - Meitlis, Iana; Allenspach, Eric J; Bauman, Bradly M; Phan, Isabelle Q; Dabbah, Gina; Schmitt, Erica G; Camp, Nathan D; Torgerson, Troy R; Nickerson, Deborah A; Bamshad, Michael J; Hagin, David; Luthers, Christopher R; et al. (Am J Hum Genet, 2020)
Genetic testing has increased the number of variants identified in disease genes, but the diagnostic utility is limited by lack of understanding variant function. CARD11 encodes an adaptor protein that expresses dominant-negative and gain-of-function variants associated with distinct immunodeficiencies. Here, we used a "cloning-free" saturation genome editing approach in a diploid cell line to simultaneously score 2,542 variants for decreased or increased function in the region of CARD11 associated with immunodeficiency. We also described an exon-skipping mechanism for CARD11 dominant-negative activity. The classification of reported clinical variants was sensitive (94.6%) and specific (88.9%), which rendered the data immediately useful for interpretation of seven coding and splicing variants implicated in immunodeficiency found in our clinic. This approach is generalizable for variant interpretation in many other clinically actionable genes, in any relevant cell type.
Keywords: Adenine; B-Cell CLL-Lymphoma 10 Protein; B-Lymphocytes; CARD Signaling Adaptor Proteins; Cell Line; Diploidy; Exons; Genes, Dominant; Genetic Variation; Guanylate Cyclase; Humans; Immunologic Deficiency Syndromes; Jurkat Cells; Lymphoma; NF-kappa B p50 Subunit; Piperidines; Polymorphism, Single Nucleotide; Primary Immunodeficiency Diseases; Sensitivity and Specificity